Role of peroxiredoxin 2 in [H.sub.2][O.sub.2]-induced oxidative stress of primary Leydig cells - Duan, Ting; Fan, Kai; Chen, Shengrong; Yao, Qi; Zeng, Rong; Hong, Zhiwei; Peng, Longping; Shao, Yong; Yao, Bing (Molecular medicine reports, 2016)
Late-onset hypogonadism is defined as a condition caused by a decline in the levels of testosterone with aging. One of the major factors contributing to the low levels of testosterone is the accumulation of reactive oxygen species (ROS) in Leydig cells during the ageing process. Peroxiredoxin 2 (Prdx2), a member of the peroxiredoxin family, is an antioxidant protein, the predominant function of which is to neutralize ROS. However, its role in Leydig cells remains to be elucidated. In the present study, primary Leydig cells were exposed to low concentrations of hydrogen peroxide ([H.sub.2][O.sub.2]) to induce oxidative stress. Cell apoptosis was measured using an Annexin V fluorescein isothiocyanate/propidium iodide apoptosis detection kit and flow cytometry. The level of testosterone was determined by radioimmunoassay, and the mRNA and protein expression levels of Prdx2 were detected by reverse transcription-polymerase chain reaction and western blotting, respectively. The results revealed a significant increase in cell apoptosis and decrease in testosterone production. In addition, the expression of Prdx2 was decreased by [H.sub.2][O.sub.2] in a dose- and time-dependent manner, and this decrease may have been caused by the induction of its molecular structure transformation due to [H.sub.2][O.sub.2] elimination. The above findings indicated that Prdx2 may prevent [H.sub.2][O.sub.2] accumulation in Leydig cells, and may be important in oxidative stress-induced apoptosis and decreased testosterone production. Key words: late-onset hypogonadism, Leydig cells, testosterone, [H.sub.2][O.sub.2], peroxiredoxin 2